Investigating Efficiency of Vector-Valued Intensity Measures in Seismic Demand Assessment of Concrete Dams - Mohammad Alembagheri (Advances in Civil Engineering)
The efficiency of vector-valued intensity measures for predicting the seismic demand in gravity dams is investigated. The Folsom gravity dam-reservoir coupled system is selected and numerically analyzed under a set of two-hundred actual ground motions. First, the well-defined scalar IMs are separately investigated, and then they are coupled to form two-parameter vector IMs. After that, IMs consisting of spectral acceleration at the first-mode natural period of the dam-reservoir system along with a measure of the spectral shape (the ratio of spectral acceleration at a second period to the first-mode spectral acceleration value) are considered. It is attempted to determine the optimal second period by categorizing the spectral acceleration at the first-mode period of vibration. The efficiency of the proposed vector IMs is compared with scalar ones considering various structural responses as EDPs. Finally, the probabilistic seismic behavior of the dam is investigated by calculating its fragility curves employing scalar and vector IMs considering the effect of zero response values.